INTERCULTURAL COMPETENCE OF A MODERN TEACHER - Yusupova F. M. (Web of Journals Publishing, 2025)
This article describes the problem of the relevance of a teacher's intercultural competence in the context of a multinational state.
Keywords: Intercultural competence, multicultural competence, multicultural educational environment, multicultural education, cultural diversity, tolerance.